Water electrolysis anode catalyst and water electrolysis anode
A layered rock salt structure catalyst with high entropy configuration addresses the low activity of nickel-based oxides by enhancing oxygen generation in alkaline water electrolysis, achieving improved catalytic activity and stability.
Patent Information
- Application Number
- JP2023115414
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-24
AI Technical Summary
Existing nickel-based oxides used as catalysts in alkaline water electrolysis have low catalytic activity, leading to higher energy consumption for oxygen generation compared to hydrogen generation, and improvements in catalytic activity have been challenging due to issues with lattice constant increase and thermodynamic instability when introducing elements with small ionic radii or doping metals like Cu and Zn.
A catalyst with a layered rock salt structure containing multiple metal elements, achieving an entropy of configuration greater than 1.5R, which enhances oxygen generation by increasing disorder and local shortening of O-O distances and oxygen vacancy concentration, thereby improving catalytic activity and stability.
The catalyst exhibits high catalytic activity and extended lifespan for oxygen generation in alkaline water electrolysis, contributing to improved energy efficiency and stability in alkaline environments.
Smart Images

Figure 2025012527000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a catalyst for a water electrolysis anode and an anode for water electrolysis. [Background technology]
[0002] Water electrolysis is one of the industrial methods for producing hydrogen. In alkaline water electrolysis and anion exchange membrane (AEM) water electrolysis, an alkaline aqueous solution is used as the electrolyte, and nickel-based oxides are widely used as the catalytic material for the anode.
[0003] In general, nickel-based oxides have relatively low catalytic activity. Conventionally, in alkaline water electrolysis devices, the amount of energy required to advance the reaction at the anode (oxygen production reaction) is greater than the amount of energy required to advance the reaction at the cathode (hydrogen production reaction). In order to improve the energy efficiency of alkaline water electrolysis devices, materials with higher catalytic activity than nickel-based oxides have been investigated (see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-25951 Summary of the Invention [Problem to be solved by the invention]
[0005] There is a demand for improving the performance of catalysts used in anodes in water electrolysis. [Means for solving the problem]
[0006] In order to solve the above problems, a water electrolysis anode catalyst in one embodiment of the present disclosure is a catalyst used in an anode for water electrolysis, which includes a first composite oxide having a layered rock salt structure and containing multiple metal elements other than alkali metal elements and one or more alkali metal elements, and has an entropy of configuration determined by the number of types of the multiple metal elements and their respective proportions greater than 1.5R (R is the gas constant). Effect of the Invention
[0007] According to one aspect of the present disclosure, it is possible to improve the performance of a catalyst used in an anode in a water electrolysis process. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram for explaining a catalyst in one embodiment of the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram showing an anode for water electrolysis in one embodiment of the present disclosure. [Diagram 3] FIG. 1 is a schematic diagram for explaining a general rock-salt structure. [Figure 4] FIG. 2 is a schematic diagram for explaining a layered rock-salt structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described. In order to facilitate understanding of the catalyst in the present embodiments, first, the novel findings of the present inventors will be briefly described.
[0010] <Brief Description of the Findings of the Invention> Conventionally, for example, α-NaFeO2 type oxides (also called layered rock salt type oxides) have been proposed as catalytic materials for anodes. FIG. 3 is a schematic diagram for explaining a general rock salt type structure. FIG. 4 is a schematic diagram for explaining a layered rock salt type structure. A general rock salt type structure (cubic rock salt type structure) is as follows: <111> It can be said that this is a layered structure in which metal atomic layers M and oxygen atomic layers O are regularly arranged in the axial direction (see Fig. 3). On the other hand, a "layered rock-salt structure" has a structure in which unequal metal atomic layers M1 and M2 exist, and each element is regularly arranged as M1, O, M2, O, M1, O, M2, O, ... (see Fig. 4). As a specific example, NaFeO2 with a layered rock-salt structure has a cubic rock-salt structure. <111> Orientation (layered salt structure) <001> In other words, NaFeO2, which has a layered rock-salt structure, has a Na layer where Na is two-dimensionally arranged, an O layer where O is two-dimensionally arranged, an Fe layer where Fe is two-dimensionally arranged, and another O layer, which are arranged in a regular order in the cubic rock-salt structure. <111> It has a structure that is periodically arranged in the direction.
[0011] More specifically, for example, NaFeO2 having a layered rock-salt structure has a layered structure in which a plurality of basic layers are laminated, with a portion consisting of an Fe layer (metal atomic layer M2 in the example of FIG. 4) and two adjacent O layers as the basic layer, and a Na layer (intermediate layer, metal atomic layer M1 in the example of FIG. 4) is inserted between the laminated basic layers. Typically, in the basic layer, a plurality of [FeO6] octahedra are arranged two-dimensionally by sharing edges, and one side of a square formed by connecting four of the six vertices of the octahedra is shared between adjacent [FeO6].
[0012] It has been reported that layered rock-salt oxides exhibit high catalytic activity in the anode oxygen evolution reaction due to the relatively short O-O distance (see, for example, the references below); [Hao Wang et. al., "Short OO separation in layered oxide Na 0.67CoO2enables an ultrafast oxygen evolution reaction", Proc. Natl. Acad. Sci. USA, (November 19, 2019), Vol.116, No.47, 23473-23479].
[0013] In order to improve the catalytic activity in the oxygen evolution reaction at the anode, it is expected that it would be effective to further shorten the OO distance in the structure of the layered rock-salt oxide. For example, one possible measure would be to further shorten the OO distance (corresponding to the size of the octahedron) by dissolving an element with a relatively small ionic radius in the cation site of the basic layer (e.g., the Fe site in NaFeO2).
[0014] However, when the inventors tried the above measures, they found that when an element with a small ionic radius is simply dissolved in a layered rock-salt oxide, the lattice constant of the layered rock-salt structure tends to increase, although the reason is unclear. As a result of the increase in the lattice constant, the O-O distance increases, and no significant improvement in catalytic activity was observed. In addition, for example, dissolving Al, which has a relatively small ionic radius, in the Fe site is thermodynamically unstable, and it is difficult to simply increase the amount of Al dissolved in the layered rock-salt oxide.
[0015] In addition, the oxygen generation reaction involves the addition of OH to the catalyst surface. - Therefore, the adsorption of OH is required to improve the catalytic activity in the anode oxygen evolution reaction. - It is expected that it will also be effective to introduce oxygen vacancies, which serve as adsorption sites for oxygen, into the catalyst material. One possible way to introduce oxygen vacancies is to dope the Fe sites in the layered rock salt structure with low-valent metals such as Cu and Zn. However, doping the trivalent Fe sites with divalent Cu or Zn (for example, by replacing Fe in NaFeO2) is thermodynamically unstable. Therefore, there are problems such as the inability to increase the amount of low-valent metals such as Cu and Zn in solid solution, which does not improve catalytic activity, or the increase in the amount of low-valent metals in solid solution shortens the catalyst life.
[0016] Thus, in the case of layered rock-salt-type oxides, even if an element with a relatively small ionic radius is dissolved in order to improve the catalytic activity in the oxygen evolution reaction at the anode, the lattice constant tends to become larger, and it has been difficult to reduce the OO distance or introduce many oxygen vacancies by a simple method. In other words, it is not easy to concretely realize a measure to improve the catalytic activity of layered rock-salt-type oxides in the oxygen evolution reaction at the anode. While various candidates for catalytic materials used in the oxygen evolution reaction at the anode have been investigated for improving the catalytic activity, the promise of layered rock-salt-type oxides has been unclear.
[0017] By the way, in recent years, research has been conducted on high entropy materials. For example, in high entropy alloys, due to the high entropy effect, it is easy to generate solid solutions in which elements are randomly distributed, and effects due to the disorder of the arrangement of metal elements and the effects due to the interaction between different metal elements are expected. In high entropy alloys, the higher the entropy, the better the properties, and the composition with the desired high properties is only a part of the wide variety of combinations of elements. Therefore, it is not easy to predict the physical properties of high entropy alloys. For high entropy oxides, it is even more difficult to predict the physical properties. This is because, unlike alloys, oxides have crystal structures and solid solution sites of different elements based on the coordination relationship of each element, so the effects of structural changes due to high entropy are considered to be complex, and it is difficult to predict the effects of high entropy.
[0018] As a result of extensive research, the present inventors have found the following and arrived at the present invention. That is, by making the metal elements in the basic layer in the layered rock-salt structure multi-element so that they have a larger entropy of configuration than a certain level, it is possible to improve the catalytic activity in the oxygen evolution reaction at the anode, although the details are not yet clear. In addition, by solving the above-mentioned problems, it is possible to further improve the catalytic activity.
[0019] The catalyst according to an embodiment of the present disclosure is applicable to use in an alkaline environment, for example, to an anode in a water electrolysis reaction in which an alkaline aqueous solution is used as an electrolyte. Examples of water electrolysis reactions in which an alkaline aqueous solution is used as an electrolyte include alkaline water electrolysis and anion exchange membrane water electrolysis. The catalyst according to an embodiment of the present disclosure may dissolve in an acidic atmosphere, and therefore may not be applicable to an anode in a polymer electrolyte membrane (PEM) water electrolysis reaction.
[0020] Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings. Fig. 1 is a schematic diagram for explaining a catalyst in an embodiment of the present disclosure. In Fig. 1, the figures indicated by reference numerals 1001, 1002, and 1003 are enlarged views shown in the order of enlargement, but each figure is shown in a schematic manner.
[0021] As shown in FIG. 1, the catalyst 1 in this embodiment can be typically manufactured in the form of powder 10, which is an aggregate (aggregate) of the catalyst 1. The catalyst 1 may have, for example, a particle shape. In the diagram indicated by reference numeral 1002 in FIG. 1, the catalyst 1 is illustrated as a round particle in a plan view for clarity, but the specific shape of the catalyst 1 is not particularly limited. As shown in the diagram indicated by reference numeral 1003 in FIG. 1, the catalyst 1 has a plurality of crystallites 5 in the microstructure. The crystallites 5 may be a composite oxide.
[0022] The catalyst 1 in this embodiment contains a first composite oxide, which has a layered rock-salt structure and contains a plurality of metal elements other than alkali metal elements and one or more alkali metal elements. The layered rock-salt structure may be a trigonal layered rock-salt structure (space group: R-3m) or a monoclinic layered rock-salt structure (space group: C2 / m). The first composite oxide can be represented by the following general composition formula (1) or (2).
[0023] A(M G )O2(1) A2(M G )O3(2) Here, A corresponds to one or more of the above-mentioned alkali metal elements, and M G corresponds to multiple metal elements other than the above-mentioned alkali metal elements. As mentioned above, the layered rock-salt structure is a layered structure having stacked basic layers and intermediate layers located between the stacked basic layers. The above formula (1) is the composition formula of the trigonal layered rock-salt structure, and the above formula (2) is the composition formula of the monoclinic layered rock-salt structure (Li2MnO3 type structure).
[0024] In the first composite oxide represented by the above formula (1), A and M G are equimolar to each other (i.e. A:M G =1:1) and may be substantially equimolar to each other. In this case, the number of moles of A is the sum of the one or more alkali metal elements, and M G The number of moles of A and M is the sum of the above metal elements. G and are substantially equimolar to each other, A and M G This means that the molar ratio of A to M may be in the range of 90:110 to 110:90. In addition, A may be deficient from the stoichiometric composition as long as the trigonal layered rock salt structure is maintained. For example, G The molar ratio to may be 0.5 to 1.
[0025] In the first composite oxide represented by the above formula (2), A2 and M G and are equimolar to each other (i.e. A2:M G =1:1) and may be substantially equimolar to each other. In this case, the number of moles of A2 is the sum of the one or more alkali metal elements, and M G The number of moles of A2 and M is the sum of the above metal elements. G and are substantially equimolar to each other, A2 and M G This means that the molar ratio of A to M may be in the range of 90:110 to 110:90. In addition, A may be deficient from the stoichiometric composition as long as the monoclinic layered rock salt structure is maintained. For example, M of A2 G The molar ratio to may be 0.5 to 1.
[0026] In the following, M in the above formula (1) or formula (2) G These are referred to as the specific metal element group. G The specific metal element group M is composed of a plurality of metal elements selected (specified) from a group of metal elements other than alkali metal elements (Group 1) in the periodic table of elements (hereinafter simply referred to as the "periodic table"). G The metal element group to be selected is a metal element that can be located at the cation site of the basic layer in the layered rock-salt structure.
[0027] In the catalyst 1 of this embodiment, the specific metal element group M G The entropy of the configuration determined by the number of types of the above-mentioned multiple metal elements selected and their respective ratios is greater than 1.5R (R is the gas constant). The entropy of this configuration S config (Molar entropy) is a numerical value calculated by the following formula:
[0028]
number
[0029] In the above formula (3), R is the gas constant (8.314 J / (K mol)) and N is the specific metal element group M G The number of metallic elements (number of kinds) that make up i is the molar composition (molar fraction) of the i-th element. The entropy of the configuration S config In terms of calculation, if the value of N (i.e., the number of metal elements) is the same, multiple metal elements x i (i=1, 2, 3, N) are equimolar, i.e., A and M G The entropy of configuration S when and are equimolar and N is 4 config has a maximum value of approximately 1.39.
[0030] In the catalyst 1 of this embodiment, the entropy of configuration S config The first composite oxide is preferably a compound having a specific metal element group M such that N in the above formula (3) is 5 or more.G The first composite oxide may contain five or more kinds of metal elements. G The molar fractions of the multiple metal elements constituting the first composite oxide may be substantially equal to each other. "Substantially equal" means that the difference from the average of the molar fractions of the multiple metal elements is within a range of ±10%, and specifically, if the average of the molar fractions is 0.20, the molar fraction of each metal element is within a range of 0.18 to 0.22. This reduces the entropy S of configuration in the first composite oxide. config It is easy to make the value of R larger than 1.55R or 1.60R.
[0031] In addition, the first composite oxide is preferably selected from the group consisting of specific metal elements M so that N in the above formula (3) is 6 or more. G may contain six or more kinds of metal elements. This reduces the configurational entropy S config The specific metal element group M in the first composite oxide can be easily made larger than 1.6R. G The upper limit of the number of kinds of metal elements contained in is not particularly limited, but from the viewpoint of convenience in manufacturing, etc., the upper limit may be set to, for example, 10 kinds. In addition, the entropy S config The upper limit of the specific metal element group M G In relation to the provision of the above, the upper limit may be set to, for example, 2.4R. G As the number of metal elements in the system increases, the energy gain from the entropy of configuration becomes smaller, and it is necessary to mix metal elements that are incompatible (with significantly different valences or ionic radii) in order to increase the number of elements. If the energy loss due to enthalpy offsets the energy gain from the entropy of configuration, the advantage of high entropy may be lost.
[0032] Specific metal element group M G does not have to include metal elements in the seventh period of the periodic table and beryllium (Be) in the second period. This is because it is practically difficult to use metal elements in the seventh period and Be in the second period. Therefore, the specific metal element group M Gmay be a plurality of metal elements selected from the group of metal elements in the third to sixth periods of the periodic table.
[0033] In addition, the specific metal element group M G may be a plurality of metal elements selected from the group of metal elements in the third to fifth periods of the periodic table, or may be a plurality of metal elements selected from the group of metal elements in the third to fourth periods. G The larger the average ionic radius of the multiple metal elements constituting the specific metal element group M, the more unstable the layered rock salt structure may become. G The metal elements contained in the specific metal element group M are selected from the metal element group of the relatively low period of the periodic table. G The average ionic radius of the metal elements in the lower periods of the periodic table can be relatively small. Also, metal elements in the lower periods of the periodic table can be relatively cheaper than metal elements in the higher periods.
[0034] In the catalyst 1 of this embodiment, the alkali metal element contained in the first composite oxide and corresponding to A in the above formula (1) or formula (2) may be at least one of lithium (Li) and sodium (Na). The alkali metal element may be located in the intermediate layer in the layered rock-salt structure. The first composite oxide may contain both Li and Na, and in this case, the number of moles of A in the above formula (1) or the number of moles of A2 in the above formula (2) corresponds to the total number of moles of Li and Na. From the viewpoint of increasing the stability of the layered rock-salt structure in the first composite oxide, the average ionic radius of A in the above formula (1) is set to r A , M G The average ionic radius of r M The first composite oxide has a structure of r A / r M may be in the range of 1.1 to 1.8. In addition, the average ionic radius of A2 in the above formula (2) may be r A2 The first composite oxide has a structure of r A2 / r M may be in the range of 1.1 to 1.8.
[0035] The alkali metal element contained in the first composite oxide may be any element that can be positioned in the intermediate layer in the layered rock salt structure, and may be potassium (K) or rubidium (Rb). When A in the above formula (1) is K alone or Rb alone, r A / r M When r exceeds 2, the structure tends to be different from the layered rock salt structure. Therefore, the first composite oxide contains at least one of Li and Na, and A / r M may contain K or Rb within the range of 1.1 to 1.8.
[0036] In the first composite oxide, oxygen (O) in the above formula (1) is simply written as O2, but in reality, O 2-δ This can also be written as: By charge compensation, the cation A(M G This is because the amount of oxide ions, which are anions, changes depending on the valence of the oxide. In addition, in the first composite oxide, oxygen (O) in the above formula (2) is simply written as O3, but in reality, O 3-δ It can also be written as:
[0037] The catalyst 1 containing the above-mentioned first composite oxide exhibits high catalytic activity when used in an oxygen generation reaction at the anode of a water electrolysis process. Although the principle is not yet clear, in the first composite oxide, G The entropy of the configuration S config It is believed that the following effects occur when R exceeds 1.5R. In other words, the cationic sites in the basic layers of the layered rock salt structure can be highly multi-elementized. As a result, the crystal lattice becomes disordered, the distance between OO is shortened locally, and the OH groups on the catalyst surface become smaller. - It is believed that this leads to an increase in the concentration of oxygen vacancies associated with the adsorption sites of ZnO. These effects may have led to the unexpected effect of high catalytic activity in the oxygen evolution reaction at the anode of water electrolysis. Furthermore, the entropy of configuration S configWhen R exceeds 1.5R, the crystal structure is stabilized thermodynamically. As a result, it was found that the life of catalyst 1 can be extended.
[0038] In the catalyst 1 according to an embodiment of the present disclosure, the specific metal element group M G may contain transition metal elements as the multiple metal elements. Due to their electronic structure, transition metal elements can form a relatively stable composite oxide. Therefore, by using transition metal elements, the entropy of configuration S config In this specification, the transition metal elements also include elements in Group 12 of the periodic table.
[0039] In the catalyst 1 according to an embodiment of the present disclosure, the specific metal element group M G may contain a fourth period transition metal element as the multiple metal elements. There are few social restrictions on the use of elements such as fourth period transition metal elements, which are widely used in various applications, as the multiple metal elements. In this specification, the fourth period transition metal element includes zinc (Zn).
[0040] In the catalyst 1 according to an embodiment of the present disclosure, the specific metal element group M G may contain at least one of Fe, Co, and Ni as the multiple metal elements. Fe, Co, and Ni tend to act as active sites for catalytic reactions and have relatively small ionic radii. Therefore, the layered rock salt structure can be easily stabilized. As a result, the catalytic activity of the catalyst 1 can be improved. In addition, the life of the catalyst 1 can be extended.
[0041] In the catalyst 1 according to an embodiment of the present disclosure, the specific metal element group M G The first composite oxide may contain Al as one of the plurality of metal elements. configBy exceeding 1.5R, it is possible to easily dissolve Al in the solid solution. By dissolving Al in the cation sites of the basic layer, it is possible to easily reduce the lattice constant. As a result, the local crystal lattice disorder increases, making it easy to form a portion with a locally small OO distance. Therefore, the catalytic activity of catalyst 1 can be improved.
[0042] In the catalyst 1 according to an embodiment of the present disclosure, the specific metal element group M G The first composite oxide may contain at least one of Cu and Zn as the multiple metal elements. config When R exceeds 1.5R, the amount of Cu and Zn in solid solution can be increased. When divalent Cu and Zn are located at trivalent atomic sites, the oxygen vacancies contained in the catalyst can be easily increased. As a result, the catalytic activity of catalyst 1 can be improved.
[0043] Catalyst 1 may contain a first complex oxide having a layered rock-salt structure and a second complex oxide having a structure other than the layered rock-salt structure. In catalyst 1, one crystallite 5 (see the diagram indicated by reference numeral 1003 in FIG. 1) may correspond to either the first complex oxide or the second complex oxide, or one crystallite 5 may contain both the first complex oxide and the second complex oxide. The second complex oxide may have, for example, a cubic rock-salt structure.
[0044] In general, in a layered rock salt structure, an element is mixed into the intermediate layer, that is, a specific metal element group M is mixed into the site where the element A in the above formula (1) is located. G The phenomenon of contamination (disorder) of the metal elements of the specific metal element group M is known. Such a phenomenon may occur in the catalyst 1 of the present embodiment. G In this way, in the first composite oxide, A (alkali metal element) in the above formula (1) is mainly located in the intermediate layer, and the specific metal element group MG are mainly located at the cation sites of the above-mentioned basic layer. However, even if the first composite oxide has the above-mentioned disorder, it is sufficient as long as it has a layered rock salt structure as a whole. It is possible that the disorder in the first composite oxide contributes to improving the catalytic activity.
[0045] In addition, in the cubic rock-salt structure, Li + OrNa + enters the transition metal site. In this case, Li + OrNa + Since the ionic radius of the second complex oxide is relatively large, the OO distance is large. As a result, the second complex oxide with a cubic rock-salt structure may have a lower catalytic activity than the first complex oxide with a layered rock-salt structure. In addition, the catalyst material for use as a water electrolysis anode is required to have high electronic conductivity. In a layered rock-salt structure, the transition metal layer contributes to electronic conduction. On the other hand, in a cubic rock-salt structure, the Li layer, which does not play a role in electronic conduction, + OrNa + are randomly inserted into the crystal. Therefore, the second complex oxide having a cubic rock-salt structure may have lower electronic conductivity than the first complex oxide having a layered rock-salt structure.
[0046] In the catalyst 1 according to an embodiment of the present disclosure, the ratio of the first composite oxide to the total of the first composite oxide and the second composite oxide may be 0.3 or more. In addition, in the catalyst 1, the ratio of the first composite oxide may be 0.8 or less. The ratio of the first composite oxide can be specified as follows. That is, the ratio of the first composite oxide in the catalyst 1 is taken as the degree of ordering, and this degree of ordering can be calculated by subjecting the catalyst 1 to X-ray diffraction measurement and performing Rietveld analysis on the obtained pattern. For the Rietveld analysis, known software for Rietveld analysis can be used.
[0047] (Anode for water electrolysis) The anode for water electrolysis in one embodiment of the present disclosure will be described with reference to Fig. 2. Fig. 2 is a schematic diagram showing an anode 20 for water electrolysis.
[0048] 2, the water electrolysis anode 20 includes a catalyst layer 21 containing a catalyst 1, and a conductive substrate 23 supporting the catalyst layer 21. The water electrolysis anode 20 may include a functional layer 22 between the catalyst layer 21 and the conductive substrate 23.
[0049] The water electrolysis anode 20 may use a known conductive substrate 23 and functional layer 22. The specific material and shape of the conductive substrate 23 are not particularly limited. By forming the catalyst layer 21 on the surface of the functional layer 22, the stability of the catalyst layer 21 is improved. The catalyst layer 21 can be formed, for example, by applying an aqueous solution in which the catalyst 1 is dispersed to the surface of the functional layer 22, and baking the applied solution.
[0050] (Manufacturing method) Next, a method for producing the catalyst of the present embodiment will be described. The catalyst of the present embodiment can be produced by a spray pyrolysis method. Specifically, the method for producing the catalyst of the present embodiment may include a solution preparation step and a pyrolysis step.
[0051] In the solution preparation step, an alkali metal element and a specific metal element group M are mixed so as to obtain a desired metal element ratio. G In more detail, a salt of an alkali metal element (e.g., a nitrate salt) and a specific metal element group M are dissolved in ion-exchanged water to prepare a solution. G A solution is prepared by dissolving salts (eg, nitrates) of multiple metal elements selected as the metal salts in ion-exchanged water.
[0052] In the pyrolysis step, first, ultrasonic waves are applied to the solution prepared in the solution preparation step to atomize the solution. Next, the atomized solution is introduced into a tubular furnace heated to a high temperature (e.g., 800°C) using air as a carrier gas, and pyrolyzed inside the tubular furnace. This allows the catalyst of this embodiment to be produced. The catalyst produced by pyrolysis is collected, for example, by a filter.
[0053] (Other configurations) In one embodiment of the present disclosure, the catalyst 1 contains an alkali metal element and a specific metal element group M G The catalyst 1 may contain an element other than the above (hereinafter, for convenience of explanation, referred to as "unspecified element"). The catalyst 1 may contain the unspecified element as an inevitable impurity. The catalyst 1 may contain the unspecified element to the extent that it does not significantly affect the catalytic activity, and may contain, for example, 1 mol % or less of the unspecified element in the total amount of substance of the first composite oxide. In the catalyst 1 according to one embodiment of the present disclosure, when the first composite oxide contains the unspecified element, it is sufficient that the remainder obtained by subtracting the amount of substance of the unspecified element from the total amount of substance of the first composite oxide satisfies the various conditions for the catalyst 1 described above.
[0054] Moreover, the molar fraction of each element in the catalyst 1 according to the embodiment of the present disclosure may be understood as the molar fraction in the charge composition in the solution preparation step of the above-mentioned production method. The present inventors have confirmed through experiments that the difference between the molar fraction in the charge composition and the molar fraction contained in the actually produced catalyst is relatively small.
[0055] <Summary> The anode catalyst for water electrolysis in aspect 1 of the present disclosure is a catalyst used in an anode for water electrolysis, which includes a first composite oxide having a layered rock salt structure and containing multiple types of metal elements other than alkali metal elements and one or more types of alkali metal elements, and has an entropy of configuration determined by the number of types of the multiple metal elements and their respective proportions greater than 1.5R (R is the gas constant).
[0056] In the anode catalyst for water electrolysis according to a second aspect of the present disclosure, in the first aspect, the plurality of metal elements include a fourth period transition metal element.
[0057] In the anode catalyst for water electrolysis according to a third aspect of the present disclosure, in the first or second aspect, the plurality of metal elements include at least one of Fe, Co, and Ni.
[0058] The water electrolysis anode catalyst according to Aspect 4 of the present disclosure is any one of Aspects 1 to 3, wherein the plurality of metal elements further includes Al.
[0059] In a fifth aspect of the present disclosure, in the anode catalyst for water electrolysis according to any one of the first to fourth aspects, the plurality of metal elements include at least one of Cu and Zn.
[0060] The anode catalyst for water electrolysis according to embodiment 6 of the present disclosure is, in any one of embodiments 1 to 5, a second composite oxide having a structure other than a layered rock-salt structure, and a ratio of the first composite oxide to a total of the first composite oxide and the second composite oxide is 0.3 or more.
[0061] The water electrolysis anode according to a seventh aspect of the present disclosure includes a catalyst layer including the water electrolysis anode catalyst according to any one of the first to sixth aspects, and a conductive substrate supporting the catalyst layer.
[0062] [Additional notes] The invention according to the present disclosure has been described above based on the drawings and embodiments. However, the invention according to the present disclosure is not limited to the above-mentioned embodiments. In other words, the invention according to the present disclosure can be modified in various ways within the scope of the present disclosure, and embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the invention according to the present disclosure. In other words, it should be noted that a person skilled in the art can easily make various modifications or corrections based on the present disclosure. It should also be noted that these modifications or corrections are included in the scope of the present disclosure.
[0063] According to one aspect of the present disclosure, it is possible to improve the performance of a catalyst used in an anode in a water electrolysis process. This is expected to contribute to the promotion of a hydrogen society. Such an effect will also contribute to the achievement of, for example, Goal 7 of the Sustainable Development Goals (SDGs) advocated by the United Nations, "Affordable and Clean Energy." EXAMPLES
[0064] An example of a catalyst according to one embodiment of the present disclosure will be described below. The following example is an example for confirming the effects of the present disclosure.
[0065] <Example 1> The catalyst of Example 1 was prepared as follows. First, LiNO3, Cr(NO3)3·9H2O, Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O were dissolved in 500 mL of ion-exchanged water to prepare a solution such that the molar fractions of Li, Cr, Mn, Fe, Co, and Ni were Li:Cr:Mn:Fe:Co:Ni=1:0.2:0.2:0.2:0.2:0.2. The solution was adjusted so that the total concentration of metal elements was 0.1 mol / L.
[0066] Next, ultrasonic waves were applied to the prepared solution to atomize the solution. Next, the atomized solution was introduced into a tubular furnace heated to 800°C using 3 SLM (SLM is an abbreviation for standard liter per minute, and is a unit of gas flow rate expressed in L / min at 0°C and 101.3 kPa) of air as a carrier gas, and thermally decomposed inside the tubular furnace to produce a powdered catalyst of Example 1. The produced catalyst was collected by a filter.
[0067] <Example 2> The catalyst of Example 2 was prepared using the same method as the catalyst of Example 1, except that NaNO3 was used instead of the starting material LiNO3, and a solution was prepared by dissolving each raw material in 500 mL of ion-exchanged water so that the molar fraction was Na:Cr:Mn:Fe:Co:Ni=1:0.2:0.2:0.2:0.2:0.2.
[0068] <Example 3> The catalyst of Example 3 was prepared using the same method as the catalyst of Example 1, except that Al(NO3)3·9H2O was used instead of the starting material Ni(NO3)2·6H2O, and a solution was prepared by dissolving each raw material in 500 mL of ion-exchanged water so that the molar fraction was Li:Al:Cr:Mn:Fe:Co=1:0.2:0.2:0.2:0.2:0.2.
[0069] <Example 4> The catalyst of Example 4 was prepared in the same manner as the catalyst of Example 1, except that Cu(NO3)2·3H2O and Zn(NO3)2·6H2O were used instead of the starting materials Cr(NO3)3·9H2O and Mn(NO3)2·6H2O, and a solution was prepared by dissolving each raw material in 500 mL of ion-exchanged water so that the molar fraction was Li:Fe:Co:Cu:Zn=1:0.2:0.2:0.2:0.2:0.2.
[0070] <Comparative Example 1> The catalyst of Comparative Example 1 was prepared using the same method as the catalyst of Example 1, except that LiNO3 and Co(NO3)2·6H2O were used as starting materials and a solution was prepared by dissolving each raw material in 500 mL of ion-exchanged water so that the molar fraction of Li:Co was 1:1.
[0071] <Comparative Example 2> The catalyst of Comparative Example 2 was prepared using the same method as the catalyst of Example 1, except that NaNO3 and Co(NO3)2·6H2O were used as starting materials and a solution was prepared by dissolving each raw material in 500 mL of ion-exchanged water so that the molar fraction of Na:Co was 1:1.
[0072] <Comparative Example 3> The catalyst of Comparative Example 3 was prepared using the same method as the catalyst of Example 1, except that LiNO3, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O were used as starting materials, and a solution was prepared by dissolving each raw material in 500 mL of ion-exchanged water so that the molar fraction was Li:Fe:Co:Ni = 1:0.33:0.33:0.33.
[0073] (Regularity evaluation method) Powder X-ray diffraction measurements were performed on each of the catalyst powders of each Example and Comparative Example. Powder XRD (X-ray diffraction) patterns were obtained at 2θ = 5 to 90° using Cu-Kα radiation. Rietveld analysis was performed on the obtained XRD patterns to calculate the molar ratio of α-NaFeO2 type structure and rock salt type structure. From this molar ratio, the proportion of α-NaFeO2 type structure was calculated, and this was taken as the degree of ordering.
[0074] (Method for evaluating catalytic activity) The catalytic activity of each of the catalysts in the examples and comparative examples was evaluated by the following method. The catalyst powder and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) and ultrasonic waves were applied for 30 minutes. This resulted in a slurry in which the catalyst powder was dispersed. The contents were adjusted to 5 g / L for the catalyst powder and 0.25 g / L for the PVDF.
[0075] 5 μL of the prepared slurry was dropped onto a rotating disk electrode made of glassy carbon and having a diameter of 5 mm, and dried at 70° C. for 1 hour, thereby obtaining a rotating disk electrode carrying the catalyst.
[0076] The catalytic activity was evaluated using a three-electrode cell with the rotating disk electrode as the working electrode, a platinum wire as the counter electrode, and Hg / HgO / 0.1M KOH (+0.894V based on the reversible hydrogen electrode) as the reference electrode. 0.1M KOH was used as the electrolyte. The temperature of the electrolyte was kept at 25°C. In addition, oxygen gas was bubbled into the electrolyte for 30 minutes before the measurement to saturate the dissolved oxygen. The rotating disk electrode immersed in the electrolyte was rotated at 1600 rpm.
[0077] The working electrode, counter electrode, and reference electrode were connected to a potentio / galvanostat, and the current density at the rotating disk electrode was set to 100 A / m 2 A voltage was applied so that the potential was measured. This state was maintained for 3 minutes, and the potential was then read. Furthermore, voltage was applied for 10 hours in this state, and the potential was also measured after 10 hours.
[0078] The results are shown in Table 1.
[0079] [Table 1]
[0080] In Table 1, a (Å) is the lattice constant determined by X-ray diffraction, and the degree of ordering (%) is the ratio of the first composite oxide having a layered rock-salt structure determined by X-ray diffraction. More specifically, a (Å) is the a-axis length in the first composite oxide having a layered rock-salt structure contained at the rate of degree of ordering (%). It can be said that the smaller a (Å) is, the smaller the average size of the octahedral portion in the basic layer of the layered rock-salt structure is, and that there are parts with relatively small OO distances locally. In addition, the E shown in Table 1 100 is a current density of 100A / m 2 is the potential when E 100 The smaller the value, the smaller the overvoltage for oxygen generation and the higher the catalytic activity. The smaller the change (difference) between the value after 10 hours of continuous current and the initial value, the longer the catalyst life.
[0081] The catalysts of Examples 1 to 4 contain a first composite oxide containing multiple metal elements other than alkali metal elements and one or more alkali metal elements, and have a configurational entropy greater than 1.5 R. This shows that the catalysts of Examples 1 to 4 have higher catalytic activity and longer life than the catalysts of Comparative Examples 1 to 3. [Explanation of symbols]
[0082] 1. Catalyst 5. Crystallite 10 powder
Claims
1. A catalyst for use in an anode of a water electrolysis process, comprising: A first composite oxide has a layered rock salt structure and contains a plurality of metal elements other than alkali metal elements and one or more alkali metal elements, A catalyst for a water electrolysis anode, wherein the entropy of configuration determined by the number of types of the plurality of metal elements and their respective ratios is greater than 1.5R (R is a gas constant).
2. The water electrolysis anode catalyst according to claim 1 , wherein the plurality of metal elements include a fourth period transition metal element.
3. The water electrolysis anode catalyst according to claim 1 , wherein the plurality of metal elements include at least one of Fe, Co, and Ni.
4. The water electrolysis anode catalyst according to claim 1 , wherein the plurality of metal elements further includes Al.
5. The water electrolysis anode catalyst according to claim 1 , wherein the plurality of metal elements include at least one of Cu and Zn.
6. A second composite oxide having a structure other than a layered rock salt structure, 2. The water electrolysis anode catalyst according to claim 1, wherein a ratio of the first composite oxide to a total of the first composite oxide and the second composite oxide is 0.3 or more.
7. 7. A water electrolysis anode comprising: a catalyst layer containing the water electrolysis anode catalyst according to claim 1; and a conductive substrate supporting the catalyst layer.
Citation Information
Patent Citations
Alkaline water electrolysis anode and production method thereof
JP2022025951A